Defining exceptional species—A conceptual framework to expand and advance ex situ conservation of plant diversity beyond conventional seed banking. (February 2022) - Pence, Valerie C.; Meyer, Abby; Linsky, Jean; Gratzfeld, Joachim; Pritchard, Hugh W.; Westwood, Murphy; Bruns, Emily Beckman
Abstract: The multiple, complex risks to plant species survival are increasing, and conservation strategies that include ex situ as well as in situ approaches are needed now more than ever. Seed banking (drying at c.15% relative humidity and then storing at −20 °C) is the most efficient and effective ex situ method for long-term conservation for a majority of plant species. However, some plant species are not amenable to this practice, and such species have been labeled exceptional . Critical limitations to conventional seed banking include: 1) the unavailability of sufficient seed for storage; 2) seeds that are completely intolerant of the drying process (recalcitrant); 3) fully or partially desiccation tolerant seeds that are short-lived or sensitive to storage in a conventional freezer; and 4) seeds exhibiting complex dormancies that significantly hinder post-storage germination. Here we describe species examples to illustrate the key features of these four factors of exceptionality. This definition of exceptionality will provide the foundation for identifying exceptional species and directing resources to the appropriate approaches needed for their conservation. The long-term ex situ conservation of exceptional species will require living collections, as well as technologies involving expertise in cryobiotechnology, seed biology, plant physiology, plant ecology, and horticulture, emphasizing the importance of fully integrating multi-disciplinary conservation actions underpinned by training and knowledge exchange. Given that the number of known exceptional species is anticipated to increase substantially with further research, we call for immediate, concerted, and focused international action to address the conservation needs of the world's exceptional plant species. Highlights: Exceptional plants cannot be effectively conserved in conventional seed banks. They pose challenges to the steps of seedbanking: collect, process, store, recover. Exceptional species are defined by an exceptionality factor based on these steps. This definition can help develop strategic conservation action for these species.